Contents and Forewords, SUSURGALUR Journal, issue of September 2015 - SUSURGALUR, Editor Journal (SUSURGALUR, 2015)
The SUSURGALUR journal, with ISSN 2302-5808, was firstly published on March 24, 2013. Since issue of September 2013, the SUSURGALUR journal has jointly been organized by the Lecturers of APB UBD (Academy of Brunei Studies, University of Brunei Darussalam) and the Lecturers of International and Historical Study Program FASS (Faculty of Arts and Social Sciences) UBD in Bandar Seri Begawan, Brunei Darussalam; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every March and September.Â Bandar Seri Begawan, Brunei Darussalam: September 30, 2015.Â Assoc. Prof. Ampuan Dr. Haji Brahim bin Ampuan Haji TengahEditor-in-Chief of the SUSURGALUR Journal in Bandung, Indonesia; and Director of APB UBD (Academy Brunei Studies, University of Brunei Darussalam) in Bandar Seri Begawan, Negara Brunei Darussalam.Â